3D atrial strain for prediction of atrial fibrillation recurrence. (3rd October 2022) - Krizanovic-Grgic, I; Anwer, S; Steffel, J; Hofer, D; Saguner, A M; Spengler, C M; Breitenstein, A; Tanner, F C
Abstract: Introduction: Atrial fibrillation (AF) is one of the most common supraventricular arrhythmias. Treatment options apart from medication include interventional catheter-guided pulmonary vein isolation (PVI). However, there is limited knowledge about factors predicting arrhythmia recurrence after PVI. Aim: To study the association of 3-dimensional (3D) left atrial (LA) strain (LAS) and 3D electro-anatomical voltage mapping (EAVM) with early recurrence of AF after PVI. Methods: In this prospective single center study, 93 patients undergoing PVI were enrolled between December 2018 and October 2021. All patients underwent an echocardiographic examination within two weeks before PVI using the Canon Aplio i900 system to analyse LAS from 3D LA volume. A 3D EAVM was obtained using high-density mapping catheters during PVI. The CARTO 3 system (Version V6-V7) was used for determining LA scar area by low voltage mapping (local amplitude <0.5 mV) indicated as percentage (EAVM-%). Follow-up time points were set at 2, 3, 6 and 12 months to investigate recurrence of AF, with exclusion of events occurring during the first two months (blanking phase). Results: During follow-up, 12 out of 93 patients experienced recurrence of AF (12.9%; AF-Group). Baseline characteristics did not differ between AF-Group and Non-AF-Group. In contrast, LAS was significantly impaired in the AF-Group (median −4.6, IQR [−5.6 to −3.6]) when compared to the Non-AF-Group (−6.2 [−8.3 to −4.5]; p=0.009). The EAVM-% did not differ between the groups (AF-Group: 5.0 [1.5 to 21.5]; Non-AF-Group: 4.4 [1.5 to 15.9]; p=0.710). No significant correlations were found between LAS and EAVM-% (r=0.03, p=0.812). A cut-off value of −5.89% for LAS had a sensitivity of 100% and a specificity of 57% for AF recurrence (AUC=70%; p<0.001). Kaplan Meier curves for event-free survival were generated based on the LAS cut-off demonstrating excellent differentiation of those with and without AF recurrence (p<0.001; see figure). Furthermore, LAS was associated with an increased risk of early AF recurrence (HR 1.40, IQR [1.02–1.92], p=0.040), while EAVM-% was not (HR 0.99 [0.95–1.04], p=0.787). Conclusion: 3D LAS was associated with an increased risk of early AF recurrence after PVI, while EAVM-% was not. 3D LAS might be used for identifying patients who would benefit from PVI. Funding Acknowledgement: Type of funding sources: None.